2021
DOI: 10.1186/s13287-021-02589-y
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic progenitor cells promote the repair of schistosomiasis liver injury by inhibiting IL-33 secretion in mice

Abstract: Background Hepatic schistosomiasis, a chronic liver injury induced by long-term Schistosoma japonicum (S. japonicum) infection, is characterized by egg granulomas and fibrotic pathology. Hepatic progenitor cells (HPCs), which are nearly absent or quiescent in normal liver, play vital roles in chronic and severe liver injury. But their role in the progression of liver injury during infection remains unknown. Methods In this study, the hepatic egg gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…To investigate the role and mechanisms of IL-33 in type 2 immune response during biliary injuries caused by C. sinensis infection, we first generated IL-33 KO mice with the same genetic background (BALB/c) using CRISPR-Cas9 gene-editing systems [ 10 ]. Then, we established a biliary injury mouse model by infection with C. sinensis for 8 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the role and mechanisms of IL-33 in type 2 immune response during biliary injuries caused by C. sinensis infection, we first generated IL-33 KO mice with the same genetic background (BALB/c) using CRISPR-Cas9 gene-editing systems [ 10 ]. Then, we established a biliary injury mouse model by infection with C. sinensis for 8 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type mice and IL-33 KO mice (BALB/c female, 6–8 weeks, weight 18–20 g) were used for the study. Wild-type mice were purchased from the Beijing Vital River Laboratory Animal Technology Co., Ltd. IL-33 KO mice were generated using CRISPR/Cas9 technology as previously published [ 10 ]. All the mice were bred and housed under specific pathogen-free conditions maintained at 23 °C ± 2 °C with 12 h light/12 h dark cycles at the animal center of Xuzhou Medical University.…”
Section: Methodsmentioning
confidence: 99%
“…β-actin serves as a cytoskeleton protein to produce filaments. [49] Compound 11's potential capacity to inhibit β-catenin expression may underlie its anti-inflammatory effects in the present investigation. Our results demonstrated that compound 11 reduced β-catenin expression in HepG2 by 0.284 fold, compared to control HepG2 cells (0.517 fold) (Figure 8).…”
Section: Western Blotting Analysis For the Quantification Of β-Cateni...mentioning
confidence: 87%
“…IL-33 is a part of the IL-1 family and is normally present in the nucleus and released into the extracellular compartment in response to tissue damage ( Bai et al., 2021 ). IL-33 plays an important role in immunity to schistosome infection, and IL-33 levels are positively correlated with the progression of egg granuloma and liver fibrosis ( Zhang et al., 2021 ). IL-33 induces macrophage M2-type polarization and releases IL-5 and IL-13 to promote liver fibrosis ( Li et al., 2019 ).…”
Section: Il-17 and Il-33 Promote Sslfmentioning
confidence: 99%
“…IL-33 contributes to the maintenance of type II immune microenvironments in the liver of schistosome-infected mice. During chronic infections, Hepatic progenitor cells (HPCs) inhibit the secretion of IL-33 to promote tissue restoration and inhibit the development of liver fibrosis ( Zhang et al., 2021 ). Tissue Transglutaminase (tTG) regulates cell death and cytoskeletal rearrangement, however, tTG is also involved in the regulation of SSLF.…”
Section: Il-17 and Il-33 Promote Sslfmentioning
confidence: 99%